Muru Awina - Bautista Luna, Alexandra Analit (2021)
Currently the Peruvian market is in full development with respect to the consumption of natural, healthy and highly nutritious products, which represents an excellent market to exploit, for this reason an important transnational company, leader in food, will enter to compete in the Peruvian market, specifically in the cereal and oat market. The first product with which it will enter the Peruvian market, consists of an oatmeal that is prepared instantly, reducing the time required for the classic preparation, which consists of boiling the oatmeal with milk or water and waiting for it to thicken. In addition, other types of ingredients are usually added such as chunked apple, cinnamon, etc., which implies more time in the kitchen. The presentation of this brand of instant oatmeal only requires adding hot water or milk. This product is also enriched with quinoa and kiwicha. Both are native cereals and are very well positioned as important food sources, with high nutritional value. The company's strategy is to provide an instant product, of excellent quality, highly nutritious, with a good taste at an acceptable price for the market.